Discount Framing, Live Commerce, and CRM Automation on Repurchase Intention through Perceived Value in Shopee and TikTok Shop Users - Livia Vandaniya; Nurul Adilawati; Moch Ilham Firmansyah; Naufal Zul Fahmi; Ika Diyah Candra Arifah (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: E-commerce platforms increasingly rely on promotional strategies, interactive shopping experiences, and automation-based Customer Relationship Management (CRM) systems. Previous studies have examined discount framing, live commerce, and CRM automation separately, without addressing their simultaneous effects on repurchase intention through perceived value, a critical gap in the digital marketing literature. Objective: Grounded in the Stimulus–Organism–Response (S-O-R) theory, this study examines the influence of discount framing, live commerce, and CRM automation on repurchase intention, with perceived value as a mediating variable, among Shopee and TikTok Shop users in Indonesia. Methods: A quantitative cross-sectional survey was administered to 424 respondents selected using purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results: The results indicate that discount framing, live commerce, and CRM automation have positive and significant effects on perceived value and repurchase intention. Furthermore, perceived value has a positive and significant effect on repurchase intention and partially mediates the relationships between discount framing, live commerce, and CRM automation and repurchase intention. Among the three stimulus variables, CRM automation demonstrated the strongest contribution to increasing perceived value, highlighting the importance of personalized communication, rapid automated responses, and relevant product recommendations in shaping positive consumer evaluations. These findings extend the application of the S-O-R theory by emphasizing that perceived value serves as an important psychological mechanism linking digital marketing stimuli to repurchase behavior. Conclusion: E-commerce platforms should optimize promotional formats, enhance live commerce interactivity, and strengthen CRM automation capabilities to maximize perceived value and sustain repurchase behavior.